Outcomes in elderly patients undergoing endovascular thrombectomy in association with premorbid Rankin Scale scores - Ippen, Franziska M.; Schregel, Katharina; Ungerer, Matthias; Feisst, Manuel; Ringleb, Peter A.; Gumbinger, Christoph K. (Frontiers in Neurology, 2024)
Background: Endovascular thrombectomy (EVT) reduces disability in patients with acute ischemic stroke (AIS); however, its efficacy in patients aged >80 years is unclear.Objectives: This study aimed to assess the impact of premorbid modified Rankin Scale (pmRS) and age on patients with AIS undergoing EVT and EVT's effect on functional outcome and mortality. Methods: This retrospective consecutive cohort study screened the Heidelberg Recanalization Registry (HeiReKa) database for patients with AIS between 1999 and 2021. Outcome was stratified by age (<80, 80-89, and ≥90 years) and pmRS score (0-2 vs. 3-5). Adjusted odds ratios for outcome and mortality at 3 months after treatment were examined. Results: Finally, 2591 patients were included (including those aged ≥90 years [n=158]). Poor functional outcome was associated with advanced age, vascular risk factors, stroke severity, and vessel status. Lower prestroke disability and age were associated with better outcome and decreased mortality. pmRS 3-5 was associated with an increased risk of mortality and worse functional outcome regardless of age. Patients aged ≥90 years with pmRS 0-2 had a significantly better outcome than those <80 years with pmRS 3-5. Conclusion: Both age and pmRS are important to assess the benefits of EVT. However, prestroke functional status might be more crucial than biological age concerning outcomes following EVT.